1982
DOI: 10.1111/j.1475-097x.1982.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for intramuscular pressure in the lower leg in man

Abstract: Intramuscular pressures in the anterior tibial and superficial posterior compartments of the lower leg were measured by the wick catheter technique in 34 healthy individuals (17 males and 17 females, mean age 42 years). The pressures were measured at rest, during and after exercise and during venous and arterial occlusion. The pressure was 1.1 (range 0.3-3.0) kPa in the anterior tibial and 0.5 (range 0.0-2.0) kPa in the superficial posterior compartment at rest. During exercise the intramuscular pressures rose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…10 Intramuscular pressures in the anterior tibial and superficial posterior compartments of the lower limb in healthy volunteers was reported in 1982. 22 Furthermore, significantly elevated subcutaneous and intramuscular tissue pressures have been found in patients with primary lymphedema. 23 Markedly elevated subcutaneous and intramuscular tissue pressures have also been reported in the postphlebitic limb.…”
Section: Discussionmentioning
confidence: 99%
“…10 Intramuscular pressures in the anterior tibial and superficial posterior compartments of the lower limb in healthy volunteers was reported in 1982. 22 Furthermore, significantly elevated subcutaneous and intramuscular tissue pressures have been found in patients with primary lymphedema. 23 Markedly elevated subcutaneous and intramuscular tissue pressures have also been reported in the postphlebitic limb.…”
Section: Discussionmentioning
confidence: 99%
“…Both PT and non-PT patients had significantly higher intramuscular and subcutaneous tissue pressures compared with normal values. 11,12 Intramuscular tissue pressure in 10 healthy limbs was 9.2 + 4.9 mmHg and corresponding subcutaneous tissue pressure 0.2 + 1.2 mmHg. In the patients' tissue pressures significantly decreased following surgery from 23.5 + 6.1 to 5.5 + 3.1 (intramuscularly) and from 9.8 + 3.2 to 0.6 + 1.1 mmHg (subcutaneously), respectively, and remained low at three months postoperatively.…”
Section: Resultsmentioning
confidence: 96%
“…The results of both studies demonstrated that compartment pressure in the calf increases as soon as the legs are placed in the Lloyd Davies position and that there is a further increase over time. The resting intramuscular pressure in the anterior tibial compartment when the subject is supine is ≈ 3–22 mmHg [34–36]. The measured compartment pressure in the elevated limb, hips, knees and ankles flexed to 60, 45 and 90°, respectively, was in the range 27–33 mmHg.…”
Section: Discussionmentioning
confidence: 99%